Tailoring platelet inhibition according to multiple electrode aggregometry decreases the rate of thrombotic complications after intracranial flow-diverting stent implantation. (10th April 2014) - Oran, Ismail; Cinar, Celal; Bozkaya, Halil; Korkmaz, Mehmet
Abstract : Background and purpose: Pretreatment with dual antiaggregant drugs is accepted as a standard step in intracranial stent implantation. The aim of this study was to determine whether tailored antiaggregant medication based on platelet reactivity testing with multiple electrode aggregometry (Multiplate) yields superior outcomes after intracranial flow-diverting stent (FDS) implantation compared with standard clopidogrel treatment. Methods: We retrospectively analyzed the following data from 100 consecutive patients: endovascular procedure characteristics, antiaggregant medications, procedural variables, and perioperative complications after FDS implantation for intracranial aneurysm. Patients were divided into two groups: uniform treatment with clopidogrel (untailored, early phase) and tailored treatment based on the results of aggregometry (late phase). Statistical comparisons included the Fisher exact test to compare categorical variables between the standard and aggregometry groups and the Mann–Whitney U test to compare ADP test values within the aggregometry group between groups receiving tailored or untailored treatment. Results: In the aggregometry group (68 patients, 71 procedures) there were 17 (25%) clopidogrel-resistant patients, according to a cut-off value of 468 area under the aggregation curve; 12 underwent FDS implantation under tailored antiaggregant medication. In the standard treatment group (32 patients, 33 procedures) there were 3 (9.1%) spontaneous thrombotic events and 1 (3.3%) technical hemorrhagic complication. In the aggregometry group there were 2 (2.8%) spontaneous hemorrhagic events and 1 (1.4%) technical ischemic complication. In the aggregometry group, thrombotic complications and morbidity were lower than in the standard (no test) group (p<0.03). Conclusions: Tailoring platelet reactivity according to multiple electrode aggregometry decreases the rate of thrombotic complications after intracranial FDS implantation.